REFORMASI, TEORI EKONOMI, DAN KEMISKINAN - Mubyarto (UGm, 2004)
For 25 years now, the pancasila economic theory has experienced "prosperity and depression". In 1980's when the economy was booming the Indonesian economists were debating seriously to recover from the severe monetary crisi, the debate become hotter because the conventional economic theory has again demonstrated its inability. In connection with the role of IMF's economists in helping Indonesia economists to rescue the crisis, various national debate took place. the authoor's brief meeting with Muhammad Yunus. Bangladesh's most prominent economist in Dacca reactivated our long time concern on the need of "native economic theory" for Indonesia which we had called Ekonomi pancasila.